Evaluating Digital Transformation within Integration Limitations using Desk-Based Analytical Case Study - Nugroho, Setiawan Arkha Ade; Wibowo, Agus (University of Science and Computer Technology, 2025)
Digital transformation in developing regions frequently encounters challenges, including inadequate infrastructure, limited system integration, and uneven digital literacy. These constraints are especially significant in local government institutions where policy readiness and system interoperability remain low. This study evaluates the effectiveness of hybrid records management as a strategy for facilitating digital transformation, despite limitations in integration. A desk-based analytical case study was conducted on the M’mbelwa District Council in Malawi, using a mixed-method exploratory design. Qualitative analysis applied the TOE Framework, UTAUT/TAM, and the Records Continuum Model, while quantitative validation used the DeLone and McLean Information Systems Success Model. The findings show that, despite the absence of formal IoT policies, the council effectively utilized basic devices, such as computers, mobile phones, and notebooks, for daily data recording and archival management. Staff capability was measured at 50 percent intermediate and 30 percent advanced, with 100 percent daily usage. Security measures included passcode protection and regular backups. Quality scores reached 4.5 out of 5 for information relevance and 4.3 out of 5 for user satisfaction, while efficiency improved by about 25 percent. The archives lifecycle, covering creation, capture, organization, and transfer to the National Archives, was implemented effectively, although disposal procedures were absent. This study demonstrates that hybrid records management can bridge the digital divide and sustain public services in low-resource contexts. The results make theoretical contributions to the digital transformation literature and provide practical guidance for policymakers facing similar infrastructural and policy challenges.